Consumers’ trust in food risks information sources, concern and awareness of food safety issues, and related behaviours: Insights from a cross-sectional study - Almaghrabi, Merfat (Progress in Nutrition, 2023)
Background and aim: Growing concerns over food safety have spread worldwide due to rising rates of food poisoning and its associated morbidity. This study focused on assessing consumers’ trust in sources of information on food safety and risks, concern about and awareness of food safety issues, and related behaviours. Methods: This cross-sectional study involved 1,301 participants and was conducted in Saudi Arabia between August and November 2022. A structured online questionnaire was sent to potential participants aged 16 years and older. The chi-squared test and Fisher’s exact test were used to assess gender differences in terms of food safety–related knowledge, concerns, and behaviours. For the analysis, the significance level was set at p <0.05. Results: Over half (58.2%) of the study participants reported complete trust in national authorities. Approximately half (50.5%) reported not trusting celebrities, bloggers, or influencers. A greater proportion of males (48.9%) than females (39.6%) believed that food products contained harmful substances (p < 0.001). There was no significant difference between genders in terms of food safety concerns (p = 0.22). Conversely, there was a significant difference between the genders in terms of behavioural changes in response to communication about food risks (p < 0.001), with more females (30.6%) than males (22.8%) reporting that they permanently changed their consumption behaviours (e.g. diet, cooking, or storage practices) because of such information at least once in their lifetimes. Most participants’ topmost cause for concern was genetically modified ingredients in food or drinks, followed by additives such as colourings, preservatives, or flavourings. Conclusions: This research’s findings can help food authorities develop guidelines that meet consumers’ demands for safer food and conduct education campaigns to increase consumers’ awareness of and interest in food safety.